High‐yield identification of pathogenic NF1 variants by skin fibroblast transcriptome screening after apparently normal diagnostic DNA testing. Issue 12 (8th November 2022) - Douben, Hannie C. W.; Nellist, Mark; van Unen, Leontine; Elfferich, Peter; Kasteleijn, Esmee; Hoogeveen‐Westerveld, Marianne; Louwen, Jesse; van Veghel‐Plandsoen, Monique; de Valk, Walter; Saris, Jasper J.; Hendriks, Femke; Korpershoek, Esther; et al.
Abstract: Neurofibromatosis type 1 (NF1) is caused by inactivating mutations in NF1 . Due to the size, complexity, and high mutation rate at the NF1 locus, the identification of causative variants can be challenging. To obtain a molecular diagnosis in 15 individuals meeting diagnostic criteria for NF1, we performed transcriptome analysis (RNA‐seq) on RNA obtained from cultured skin fibroblasts. In each case, routine molecular DNA diagnostics had failed to identify a disease‐causing variant in NF1 . A pathogenic variant or abnormal mRNA splicing was identified in 13 cases: 6 deep intronic variants and 2 transposon insertions causing noncanonical splicing, 3 postzygotic changes, 1 branch point mutation and, in 1 case, abnormal splicing for which the responsible DNA change remains to be identified. These findings helped resolve the molecular findings for an additional 17 individuals in multiple families with NF1, demonstrating the utility of skin‐fibroblast‐based transcriptome analysis for molecular diagnostics. RNA‐seq improves mutation detection in NF1 and provides a powerful complementary approach to DNA‐based methods. Importantly, our approach is applicable to other genetic disorders, particularly those caused by a wide variety of variants in a limited number of genes and specifically for individuals in whom routine molecular DNA diagnostics did not identify the causative variant.